Surgery Versus Continued Conservative Treatment for Neurogenic Thoracic Outlet Syndrome: the First Randomised Clinical Trial (STOPNTOS Trial). (July 2022) - Goeteyn, Jens; Pesser, Niels; Houterman, Saskia; van Sambeek, Marc R.H.M.; van Nuenen, Bart F.L.; Teijink, Joep A.W.
Abstract : Objective: Neurogenic thoracic outlet syndrome (NTOS) is one of the most controversial clinical entities in medicine. Several major case series have shown promising results of surgery; however, solid scientific evidence is lacking. The aim of this trial was to objectify the effect of thoracic outlet decompression (TOD). Methods: A single centre (high volume, tertiary TOS centre), non-blinded, randomised controlled trial was conducted with parallel group design. Patients with a diagnosis of NTOS refractory to conservative therapy were randomised to one of two intervention arms, receiving either a transaxillary thoracic outlet decompression (TA-TOD) or continued conservative treatment. After three months, the conservative treated group was also offered a TA-TOD. The primary outcome was change in Disability of the Arm, Shoulder and Hand (DASH) questionnaire score. Secondary outcomes were changes in Cervical Brachial Symptoms Questionnaire (CBSQ), TOS disability scale, and quality of life scores. Outcomes were assessed at baseline, three, six, and 12 months after inclusion. Results: Fifty patients were enrolled in this trial: 25 in the TA-TOD group and 25 in the continued conservative treatment group. Follow up was completed in 24 and 22 patients, respectively. At three months, there was a statistically significant difference in DASH scores (TA-TOD: mean 45.15, 95% confidence interval [CI] 38.08 – 52.21; conservative treatment: mean 64.92, 95% CI 57.54 – 72.30; p < .001). All patients in the conservative treatment group applied for surgery three months after randomisation. After surgery of the conservative treatment group, there was no statistically significant difference between the groups for all primary and secondary outcome measures. Conclusions: TA-TOD for NTOS is effective in patients who do not respond to conservative treatment. Trial register number: NL63986.100.17.